(untitled) (Research, Society and Development, 2022)
Objective: To analyze the flow of health regulation through the process of integral emission and defined referral of the counter-reference in order to ensure the effectiveness of the regional health system, the achievement of the principle of longitudinality of care and the strengthening of the health care network. Method: This is an Integrative Review, which followed the six phases of Mendes, Silveira and Galvão. Results: 10 studies included in this review that were published and/or made available from 1999 to 2020. A form has been constructed for the extraction and management of information. The information was organized through a table describing the following aspects: year of publication, authorship, journal/institution, title, country of study and type of publication. The studies on the subject covered studies of quantitative, qualitative or qualitative approach, and with similar objects of study on the organization of access flows to health services. Conclusion: The studies show that accessibility is a ubiquitous challenge and deficiencies in the entrance door hinder the achievement of the other essential attributes of Primary Health Care.